Perceived Benefits And Barriers Of E-Commerce Among SME In Melaka's Manufacturing Industry - Peter, Ong Gim Teck (2002)
Instead of the usual deep-rooted of internal functional problems facing by SME, this research is focused primarily on the external environment factor - E-Commerce phenomenon. The main objective of this investigative study is to study the influence and relationship between perceived benefits and perceived barriers; adoption of E-Commerce; and annual sales turnover with five main hypotheses.Besides that, this paper determines to offer a contributing viewpoint to recommend ways to overcome the perceived barriers of E-Commerce and lower adoption level of E-Commerce among SME in Melaka's manufacturing industry.